Mechanics IUTAM USNC/TAM A History of People, Events, and Communities - Herakovich, Carl T. (Springer International Publishing : Imprint: Springer, 2016)
This book provides a detailed history of the United States National Committee on Theoretical and Applied Mechanics (USNC/TAM) of the US National Academies, the relationship between the USNC/TAM and IUTAM, and a review of the many mechanicians who developed the field over time. It emphasizes the birth and growth of USNC/TAM, the birth and growth of the larger International Union of Theoretical and Applied Mechanics (IUTAM), and explores the work of mechanics from Aristotle to the present. Written by the former Secretary of USNC/TAM, Dr. Carl T. Herakovich of the University of Virginia, the book profiles luminaries of mechanics including Galileo, Newton, Bernoulli, Euler, Cauchy, Prandtl, Einstein, von Kármán, Timoshenko, and in so doing provides insight into centuries of scientific and technologic advance. Profiles the applied mathematicians and engineers who developed the field of mechanics in the context of the establishment of the USNC/TAM and the IUTAM Details the relationship between USNC/TAM and IUTAM Traces the significant developments in the field of mechanics Examines the development of the USNC/TAM from its birth to the present.